ANALISIS KINERJA BANK MUAMALAT INDONESIA (BMI) DENGAN PENDEKATAN SYARIAH MAQSHID INDEX (SMI) - DEPI PUTRI WAHYUNI; ROMI ADETIO SETIAWAN; MAKMUR MAKMUR (IAIN BONE, 2025)
This study aims to analyze and evaluate the performance of Bank Muamalat Indonesia (BMI) during the 2019–2023 period using the Sharia Maqasid Index (SMI). The research applies a descriptive quantitative approach with secondary data obtained from BMI’s annual reports. The analysis was conducted using the index number method developed by Mohammed et al. (2008), covering three maqasid shariah dimensions: Tahdzib al-Fard (individual education), Iqamah al-Adl (establishing justice), and Jalb al-Maslahah (realizing welfare). The results reveal that BMI’s performance remains fluctuating, with the highest score in 2022 (0.9210) and a significant decline in 2023 (0.4235). The justice dimension appeared as the strongest, while individual education and welfare showed persistent weaknesses due to the lack of sustainable human resource development, limited zakat and CSR distribution, and insufficient financing for the real sector. These findings indicate that BMI’s implementation of maqasid shariah has not been consistent and requires strategic improvement. The recommended strategies include consistent budget allocation for training and Islamic financial literacy programs, strengthening the role of the Sharia Supervisory Board to enhance transparency in financing, and expanding social contributions through zakat, CSR, and financing in productive sectors such as SMEs and the halal industry. By adopting these measures, Islamic banking is expected to become not only financially competitive but also socially relevant and sustainable.